Infective calcified amorphous tumor on mitral valve and critical course of left ventricular rupture. Issue 4 (October 2021) - Handa, Kazuma; Fukui, Shinya; Shirakawa, Yukitoshi; Sakamoto, Tomohiko; Kitahara, Mutsunori; Kakizawa, Yumi; Nishi, Hiroyuki
Abstract: Calcified amorphous tumor is a rare intracavitary cardiac lesion and an accompanying infection is extremely rare. A 76-year-old woman was transferred to our hospital because of cerebral infarction. Echocardiography and chest computed tomography showed a calcified large mobile mass on the posterior mitral valve that was diagnosed with a calcified amorphous tumor. Moderate aortic regurgitation and severe mitral regurgitation were also confirmed. Her blood culture detected Gamella sp. We surgically dissected this infective calcified amorphous tumor. The border between this infective tumor and the mitral annulus was unclear because of severe infection and necrotic tissue. After careful complete resection, the healthy ventricular muscle was exposed and we performed annular reconstruction with bovine pericardial patches. And we replaced the aortic and mitral valves using bioprosthesis. While weaning from cardiopulmonary bypass, however, left ventricular rupture occurred twice. Despite successful repair of left ventricular rupture, which controlled bleeding, she died from multi-organ failure on postoperative day 6. An infective calcified amorphous tumor in such a critical case has not been reported previously. The calcified amorphous tumor probably become serious when the infection occurred. In this situation, the utmost caution should be paid to the patient. <Learning objective: Calcified amorphous tumor (CAT) is a rare non-neoplastic intracavitary cardiac lesion. There have been some reports of CATs but they are extremely rare with accompanying infection or critical situations. Our patient was a 76-year-old female with infective CAT who suffered from cerebral infarction, and she died from multi-organ failure despite best surgical treatment. CAT probably become serious when the infection occurred. In this situation, the utmost caution should be paid to the patient.>